MIKROORGANISME PENDEGRADASI TPH (TOTAL PETROLEUM HYDROCARBON) SEBAGAI AGEN BIOREMEDIASI TANAH TERCEMAR MINYAK BUMI (Review Article) - Prasetyo Handrianto (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2018)
Exploitation and exploration activities will produce sewage sludge and crude oil spills that cause pollution to the environment and upgrading to the environment, biology and soil chemistry. Monitoring of oil pollution conditions on the soil can be done by detection of all hydrocarbon components, or what is called the total petroleum hydrocarbon (TPH). According to its components, this total petroleum hydrocarbon (TPH) can be classified into 3 points, aliphatic, alicyclic, and aromatic. One of the biological efforts that can be used to overcome petroleum pollution is by using bioremediation technology. There are several methods in bioremediation, one of which is the biostimulation method, where the growth of the original hydrocarbon decomposers is stimulated by adding nutrients, oxygen, pH optimization and temperature. Hydrocarbonoclastic microorganisms have characteristic not possessed by other microorganisms, namely their ability to excrete hydroxylase enzymes, which are hydrocarbon oxidizing enzymes, so that these bacteria can degrade petroleum hydrocarbons. Biodegradation can be formed if there is a structural transformation so that cahnges in molecular integrity occur. This process is a series of enzymatic or biochemical reaction that require ideal environmental conditions with the growth and proliferation of microorganisms. Something that need to be known before remediation are pollutants (organic or inorganic), degraded/ not, dangerous/ not, how many pollutants pollute the soil, the ratio of carbon (C), Nitrogen (N), and phophorus (P), soil type, soil conditions (wet dry), and how long pollutants have been deposited in these locations